Gradual pressure-induced enhancement of magnon excitations in CeCoSi - Nikitin, S. E. (2020)
CeCoSi is an intermetallic antiferromagnet with a very unusual temperature-pressure phase diagram: at ambient pressure it orders below TN = 8.8 K, while application of hydrostatic pressure induces a new magnetically ordered phase with exceptionally high transition temperature of ∼40 K at 1.5 GPa. We studied the magnetic properties and the pressure-induced magnetic phase of CeCoSi by means of elastic and inelastic neutron scattering (INS) and heat capacity measurements. At ambient pressure CeCoSi orders into a simple commensurate AFM structure with a reduced ordered moment of only mCe = 0.37(6)μB. Specific heat and low-energy INS indicate a significant gap in the low-energy magnon excitation spectrum in the antiferromagnetic phase, with the CEF excitations located above 10 meV. Hydrostatic pressure gradually shifts the energy of the magnon band towards higher energies and the temperature dependence of the magnons measured at 1.5 GPa is consistent with the phase diagram. Moreover, the CEF excitations are also drastically modified under pressure.